CURBING THE MENACE OF HUMAN TRAFFICKING IN NIGERIAN COMMUNITIES - MARY OLUFUNKE, ADEDOKUN (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2016)
This paper examined the menace of human trafficking in the Nigerian Communities with emphasis on two local Government areas, one in Ekiti and one in Oyo State. Three research questions and three hypotheses were formulated to guide the study. The study was a descriptive survey research design and the population consisted of all the wards in the two chosen local government areas in Ekiti and Oyo States. Stratified random sampling technique was used to collect data rated on a four point Likert scale and on the items related to the study. The instrument was tested for reliability using Pearsons Product Moment Correlation coefficient which yielded an index of 0.79 which was adjudged good enough for measuring the consistency of the items. Mean and Standard Deviation were used to answer the research questions while t-test was used to test the hypotheses at 0.05 level of significance. The study revealed that people both, young ,men and women are victims of human trafficking, it also revealed that poverty, greed and materialism are the main causes for falling victim of human trafficking. It was also found that traffickers use violence, threat, deception and debt bondage to trap victims. It was then recommended that community education should be embarked upon to make people aware of the menace of human trafficking, job opportunities should be created for the Nigerian youth and laws should be effectively enforced on human traffickers while rehabilitaive services should be adequately provided for the victims..